Impact of priming on global soil carbon stocks. (19th February 2018) - Guenet, Bertrand; Camino‐Serrano, Marta; Ciais, Philippe; Tifafi, Marwa; Maignan, Fabienne; Soong, Jennifer L.; Janssens, Ivan A.
Abstract: Fresh carbon input (above and belowground) contributes to soil carbon sequestration, but also accelerates decomposition of soil organic matter through biological priming mechanisms. Currently, poor understanding precludes the incorporation of these priming mechanisms into the global carbon models used for future projections. Here, we show that priming can be incorporated based on a simple equation calibrated from incubation and verified against independent litter manipulation experiments in the global land surface model, ORCHIDEE. When incorporated into ORCHIDEE, priming improved the model's representation of global soil carbon stocks and decreased soil carbon sequestration by 51% (12 ± 3 Pg C) during the period 1901–2010. Future projections with the same model across the range of CO2 and climate changes defined by the IPCC‐RCP scenarios reveal that priming buffers the projected changes in soil carbon stocks — both the increases due to enhanced productivity and new input to the soil, and the decreases due to warming‐induced accelerated decomposition. Including priming in Earth system models leads to different projections of soil carbon changes, which are challenging to verify at large spatial scales. Abstract : Evolution of the soil carbon stock change from: (a) 1901 to 2010. (b) from 1951 to 2100 for the RCP2.6. (c) from 1951 to 2100 for the RCP8.5. In all figures, red indicates the values predicted by ORCHIDEE‐PRIM and blue by ORCHIDEE. For all figures, the thin lines are the simulations with the parameter values modified by ± 50%. For (b) and (c), the light blue and the orange lines represent the simulations performed with the climate forcings from the HadGEM, IPSL‐CM5A and MIROC‐ESM‐CH models for ORCHIDEE and ORCHIDEE‐PRIM, respectively.